Hospitalization from the patient perspective: a data linkage study of adults in Australia. (1st March 2018) - Harrison, Reema; Walton, Merrilyn; Kelly, Patrick; Manias, Elizabeth; Jorm, Christine; Smith-Merry, Jennifer; Iedema, Rick; Luxford, Karen; Dyda, Amalie
Abstract: Objective: Evidence of the patient experience of hospitalization is an essential component of health policy and service improvement but studies often lack a representative population sample or do not examine the influence of patient and hospital characteristics on experiences. We address these gaps by investigating the experiences of a large cohort of recently hospitalized patients aged 45 years and over in New South Wales (NSW), Australia who were identified using data linkage. Design: Cross-sectional survey. Setting: Hospitals in NSW, Australia. Participants: The Picker Patient Experience Survey (PPE-15) was administered to a random sample of 20 000 patients hospitalized between January and June 2014. Main outcome measure: Multivariable negative binomial regression was used to investigate factors associated with a higher PPE-15 score. Results: There was a 40% response rate (7661 completed surveys received). Respondents often reported a positive experience of being treated with dignity and respect, yet almost 40% wanted to be more involved in decisions about their care. Some respondents identified other problematic aspects of care such as receiving conflicting information from different care providers (18%) and feeling that doctors spoke in front of them as if they were not there (14%). Having an unplanned admission or having an adverse event were both very strongly associated with a poorer patient experience ( P < 0.001). No other factors were found to be associated. Conclusions: Patient involvement in decision-making about care was highlighted as an important area for improvement. Further work is needed to address the challenges experienced by patients, carers and health professionals in achieving a genuine partnership model.